Better Scripts, Better Games. - WHITE, WALKER; KOCH, CHRISTOPH; GEHRKE, JOHANNES; DEMERS, ALAN (Communications of the ACM, 2009)
The article discusses the production of video games, examining the manner in which better, smarter, and more powerful scripting languages can be developed. A scripting language, also called a script or extension language, is a programming language that allows some control of a single software application or many software applications. Topics include resources spent by game studios to develop tools to integrate content into software, the idea of game software as artistic content, and game-play programmers who create behavior specific to a single video game.